Integrated Nutrient Management In Brinjal - Rekha SR (Department of Agronomy, College of Agriculture, 1999)
An experiment was conducted at the Instructional Farm, Vellayani during. the period from July to November, 1998. The objective of the experiment was to study the combined effect of organic manures, chemical fertilizers and biofertilizers on the productivity and quality of brinjal and to assess the possibility of substitution of fertilizers by organic manures and biofertilizers. Two sources of nitrogen, three types of organic manures, one Azospirillum treatment and two control treatments were tried in the experiment. The result of the study showed that growth characters viz., plant height, number of leaves and branches and LAI were significantly increased by poultry manure application. Integrated application of organic and inorganic sources recorded significantly higher values for all the growth characters. Yield attributes like time to 50 per cent flowering was considerably lowered by the application of 100 per cent organic source and by the poultry manure treatments. Poultry manure treated plots showed maximum number of flowers and fruits leading to maximum fruit set percentage. Marketable fruit yield per ha was found to be maximum for treatments receiving organic and inorganic sources at 1: 1 ratio and for poultry manure applied plots. The same trend was noticed in keeping quality of fruits at ambient temp~r.ature. The economics of cultivation revealed that whatever be the type of organic manure used, when it is applied along with chemical source in 1: 1 ratio the net returns and benefit cost ratio were maximum.